Effect of cognitive styles on visual user interface design / Natrah Abdullah @ Dolah - Abdullah @ Dolah, Natrah (Institute of Graduate Studies, UiTM, 2012)
User interface design becomes more important since museums introduce online museum to exhibit museum collections. Designing the UI based on user differences and ensures that the interface is effective is important to assist users appreciate the displayed museum collections. The purpose of this study is to design and evaluate of user interface for museum website. This thesis applied a multi-method research; an approach of research that uses multiple methods over a series of studies to accumulate evidence for achieving reliable results. It employs four major phases: (1) Background Study, (2) Framework Development, and (3) Empirical Study, and (4) UI Model Development. Background study is conducted to identify issues and current trend on user interface design of museums website. In Framework Development phase, research components are identified and theoretical basis of UI design dimensions are proposed. To verify the framework and UI design dimension, a series of empirical studies is conducted.